Interactive effects of organizational structure and performance evaluation styles on job-related tension and performance - Abdullah, Shamsul Nahar (Universiti Utara Malaysia, 1996)
Previously conflicting results of Hopwood (1972) and Otley (1978) have provided exciting research opportunities in the area of management accounting systems. A number of subsequent research projects have attempted to offer possible explanations by introducing either intervening or moderating variables. Like previous research,this study also attempted to reconcile the conflicting findings by introducing a moderating variable: organizational structure. The study followed the argument of Otley (1980) who suggested that organizational structure may have an important impact on the way in which an accounting system functions. It was hypothesized that high (low) emphasis on the budgets would be congruent in a situation of low (high) degree of decentralization. A sample consisting of middle-level managers from 139 companies listed on the Kuala Lumpur Stock Exchange was selected for data collection purposes. The findings, however, failed to confirm the presence of interactive effects of organizational structure and performance evaluation styles on job performance and job related tension. This was attributed to the poor response rate.